The subject of Special Olympics – interrogating the inclusive potentials of a sport movement from an ableism-critical perspective. Issue 10 (3rd October 2022) - Giese, Martin; Buchner, Tobias; Mihajlovic, Christopher; Oldörp, Felix
Abstract: Special Olympics (SO) have proven to be a successful movement in enabling persons with intellectual disabilities to participate in sportive competitions. In this respect, SO have claimed themselves to be a facilitator for inclusion. Yet, little research has questioned the inclusive potential and only few studies applied critical perspectives to research SO. In addressing this gap, we adopt an ableism-critical perspective to interrogate ableist structures and desirable ideals of individuals embedded in official SO papers. Applying this perspective on documents of Special Olympics Germany, we understand the SO movement as a reaction to a twofold exclusion of persons with intellectual disabilities from other areas of sport: as an exclusion from mainstream sport and second, as an exclusion from elite Paralympic sport. The results show that SO contributes to a specific, namely neoliberalist normalization of people with intellectual disabilities in society, but not so much to the guiding principle of inclusion.